An Amazon Tipping Point: The Economic and Environmental Fallout - Banerjee, Onil (2021)
The Amazon biome, despite its resilience, is being pushed by unsustainable economic drivers towards an ecological tipping point where restoration to its previous state may no longer possible. This is the result of self-reinforcing interactions between deforestation, climate change and fire. In this paper, we develop scenarios that represent movement towards an Amazon tipping point and strategies to avert one. We assess the economic, natural capital and ecosystem services impacts of these scenarios using the Integrated Economic-Environmental Modeling (IEEM) Platform linked with high resolution spatial land use land cover change and ecosystem services modeling (IEEM+ESM). This paper’s main contributions are developing: (i) a framework for evaluating strategies to avert an Amazon tipping point based on their relative costs, benefits and trade-offs, and; (ii) a first approximation of the economic, natural capital and ecosystem services impacts of movement towards an Amazon tipping point, and evidence to build the economic case for strategies to avert it. We find that a conservative estimate of the cumulative regional cost through 2050 of an Amazon tipping point would be US$256.6 billion in Gross Domestic Product. Policies that would contribute to averting a tipping point, including strongly reducing deforestation, investing in climate-adapted agriculture, and improving fire management, would generate approximately US$339.3 billion in additional wealth. From a public investment perspective, the returns to implementing strategies for averting a tipping point would be US$29.5 billion. Quantifying the costs, benefits and trade-offs of policies to avert a tipping point in a transparent and replicable manner can pave the way for evidence-based approaches to support policy action focusing on the design of regional strategies for the Amazon biome and catalyze global cooperation and financing to enable their implementation.